Validity and reliability of the ABC-6 Scale Questionnaire: Cross-cultural adaptation study among Pejeng Village elders - Mutia Pramesti, Anak Agung Istri Queen; Puspa Negara, Anak Agung Gede Angga; Saraswati, Ni Luh Putu Gita Karunia; Vittala, Govinda (Majalah Ilmiah Fisioterapi Indonesia, 2024)
Introduction : The percentage of the elderly population in Bali increased to 12.47% in 2020, leading to heightened risks and fear of falling with age. One measure to assess fear of falling is the ABC-6 Scale, which gauges self-confidence in maintaining body balance. A well-measured instrument requires good validity and reliability. Testing the validity and reliability of the questionnaire is essential to demonstrate its usefulness in measuring fear of falling and screening fall risks in the future. Methods : This study employed a descriptive survey method to assess content validity using expert evaluation and a cross-sectional design with a purposive sampling technique involving 49 subjects. Validity testing utilized Pearson product-moment correlation for construct validity and Content Validity Index for content validity assessment. Reliability testing employed Cronbach's alpha to assess internal consistency. Results : The analysis revealed good construct validity values (0.509-0.823) and excellent content validity index scores (S-CVI/Ave=0.98). Reliability analysis using Cronbach's alpha demonstrated good reliability (0.775). Conclusion : The modified Indonesian version of the ABC-6 Scale is valid and reliable for screening and evaluating fear of falling among older people.   Keywords : cross-cultural adaptation, Indonesia, ABC-6 Scale questionnaire, reliability, validity